Health in cities: is a systems approach needed? - Ana V. Diez Roux (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This paper reviews the potential utility of using the concepts and tools of systems to understand and act on health in cities. The basic elements of systems approaches and the links between cities as systems and population health as emerging from the functioning of a system are reviewed. The paper also discusses implications of systems thinking for urban health including the development of dynamic conceptual models, the use of new tools, the integration of data in new ways and the identification of data gaps, and the formulation of different kinds of questions and identification of new policies. The paper concludes with a review of caveats and challenges.